2015
DOI: 10.3168/jds.2015-9376
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of tallow and soybean oil to calf starters fed to dairy calves from birth to four months of age on calf performance and digestion

Abstract: Energy demands for calves can increase during periods of heat and cold stress. One way to potentially increase energy intake is to increase the energy density of the feed with fat. Trial 1a compared a control starter with no added fat or oil (CON) to starters with 2% tallow (TAL) and 2% soybean oil (SBO). Starters were 20% crude protein (CP) and 45 to 47% starch. Male Holstein calves that were initially 3 to 5d of age were fed a 27% CP, 17% fat milk replacer at 0.66kg of dry matter daily and fully weaned by 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
(31 reference statements)
2
34
1
Order By: Relevance
“…For instance, Araujo et al (2014) reported that fat content of starter feed had no effect on solid feed intake when providing 750 g/d of MR and using full fat soybean as a fat source in the starter feed, which is known to be highly preferred by calves . However, a similar study (Hill et al, 2015) found reduced intake when feeding starter feeds rich in fat. The different results between Araujo et al (2104) and Hill et al (2015) could be linked to the type of fat (e.g., saturation) and the way it was presented to calves.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…For instance, Araujo et al (2014) reported that fat content of starter feed had no effect on solid feed intake when providing 750 g/d of MR and using full fat soybean as a fat source in the starter feed, which is known to be highly preferred by calves . However, a similar study (Hill et al, 2015) found reduced intake when feeding starter feeds rich in fat. The different results between Araujo et al (2104) and Hill et al (2015) could be linked to the type of fat (e.g., saturation) and the way it was presented to calves.…”
Section: Resultsmentioning
confidence: 83%
“…However, a similar study (Hill et al, 2015) found reduced intake when feeding starter feeds rich in fat. The different results between Araujo et al (2104) and Hill et al (2015) could be linked to the type of fat (e.g., saturation) and the way it was presented to calves. Araujo et al (2014) used whole soybeans as a source of fat, whereas Hill et al (2015) used either tallow or soybean oil.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In the present study, adding fat supplements to the CS did not affect intake of starter diets. Hill et al (22) reported that preweaning calves fed a starter diet containing tallow or soyabean oil had similar starter intake; however, postweaning, calves fed soyabean oil consumed less starter. These results are in accordance with Kadkhoday et al (46) who found that feeding starter diets with different ratios of linoleic and α-linolenic acids did not affect starter intake of Holstein dairy calves.…”
Section: Effect Of Preweaning Dietsmentioning
confidence: 99%
“…Calves born from dams supplemented with long-chain FA during the prepartum may have enterocytes with a particular FA profile that could benefit passive transfer of immunoglobulins (10) . Furthermore, strategic supplementation of EFA in MR (13,20) or calf starter (CS) (21,22) fed to preweaned calves has been reported to impact calf metabolism, improve growth, feed efficiency (FE), health, and immune status.…”
mentioning
confidence: 99%